Analisis Survei Kepuasan Masyarakat terhadap Pelayanan Publik Bidang Sosial di Kabupaten Jember - Setyohadi, Dwi Putro Sarwo; Chairina, Raden Roro Lia; Rachmanita, Risse Entikaria; Riskiawan, Hendra Yufit; Putra, Danag Eka; Firgianto, Refa (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2023)
Public service is the right of every citizen that must be fulfilled because the state is obliged to provide a number of services to fulfill the basic rights of its citizens. One of the efforts to improve the quality of public services as contained in the Law of the Republic of Indonesia Number 25 of 2000 concerning the National Development Program, all government agencies to conduct a survey on the community satisfaction index as a benchmark for assessing the level of service quality and the success of service delivery that has been implemented. done. This study aims to determine the level of satisfaction and performance of the Social Service for various types of services in the social sector based on the satisfaction index with the application of appropriate survey methods. In addition, this activity is also a way to take an inventory of various complaints and suggestions from the community. The survey results can be used as the basis for improving and improving the quality of services formulated in the follow-up plan or framework and policies by the Social Service. The study uses a quantitative approach and a qualitative approach. The quantitative approach uses the census method, while the qualitative approach uses in-depth interviews and observation methods. Respondents are people who receive public services in the social sector at the Social Service of Jember Regency. The variables used in the work of Compiling the Community Satisfaction Index (IKM) are the community's Perception and Expectation of the 9 elements of the community satisfaction index as stipulated in the PAN RB Ministerial Regulation Number 14 of 2017. The Community Satisfaction Index (IKM) value of total services the social sector in Jember Regency is 85.6 which is in category B with the quality of service performance is good.